The Influence of the Teams Games Tournament (TGT) Learning Model on the Natural and Social Sciences Studies Learning Outcomes of Grade IV Students at SD Negeri 091496 Pematang Tanah Jawa - Sirait, Dipa Martina; Panjaitan, Muktar Bahruddin; Sitio, Hetdy (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This study aims to determine whether or not there is an influence of the Teams Games Tournament learning model on the learning outcomes of fourth-grade students of SD Negeri 091496 Pematang Tanah Jawa. This type of research is quantitative research. Data collection techniques used in this study are tests and documentation. The test technique used in this study is using multiple-choice questions as a pre-test and post-test which are worth (1) if the answer is correct and worth (0) if the answer is wrong. The test is given before and after the treatment. Data analysis techniques are carried out by normality tests and hypothesis tests. The results of the t-test show that t count is 18.460, while t table is 1.711 with a significant level (2-tailed). Because the t count value (18.460) is greater than t table (1.711), it can be concluded that there is an influence of the Teams Games Tournament learning model on the learning outcomes of fourth-grade students of SD Negeri 091496 Pematang Tanah Jawa. Thus, H? is accepted and H? is rejected.